IDENTIFIKASI POTENSI DAYA TARIK EKOWISATA AIR TERJUN SEBUAK KECAMATAN NANGA TAYAP KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Adethiya, Liyan; Erianto, .; Prayogo, Hari (JURNAL HUTAN LESTARI, 2019)
Ketapang Regency has many tourism potentials in both its diversity of resources and its nature’s beauty. Many of the tourism potentials are not widely known, one of which is Sebuak waterfall in Nanga Tayap Sub-District. The purpose of this study is to obtain data on potential attraction in Sebuak Waterfall for ecotourism in Nanga Tayap Sub-District, Ketapang Regency. The study uses survey method, while the data collection techniques are direct oservation and interviews. The respondents are determined byusing purposive sampling and are chosen from the leaders of Sebuak Village, Nanga Tayap, and from the visitor of the waterfall. The result of this study indicates the tourism attraction with data of biological potential, such as various kinds of flora like mosses, pine trees, rattan, Nepenthes (tropical pitcher plants), mushrooms, and various kinds of fauna such as clown fish, shrimp, birds, butterflies, snakes, grasshoppers, non-biological potential namely the waterfall, views from above and from above and from below the waterfall, water condition in the waterfall it self and the next one is the culture around Sebuak Waterfall. Activities that can be done at Sebuak Waterfall are fishing, tracking, swimming, camping, and education. The results of the identification of the potential elements supporting eco-tourism such as its natural beauty in the form of recretional activities, air cleanliness, security, convenience, accessibility, infrastructure and accommodation of identified criteria, it can be concluded that Sebuak Waterfall is quite good and potential to be a naturetourism destination, because it can be seen from its natural beauty and the convenience of being around Sebuak Waterfall, but there are still many aspects of tourism that must be addressed, such as accessibility, accommodation, facilities and social economic conditions of the local community, so that Sebuak Waterfall can be a nature tourism attractions.Keywords: Ketapang, Nanga Tayap Village, Tourism Potential, Sebuak Waterfall.